Clinical researchDevelopmental dysplasia of the hip – angle trends after operation in different age groups - Milasinovic, Sonja; Brdar, Radivoj; Petronic, Ivana; Nikolic, Dejan; Cirovic, Dragana (Archives of Medical Science, 2010)
Introduction : The aim of our study was to evaluate changes in collodiaphyseal, Hilgenreiner and Wiberg’s centre-edge angle values in different age groups of children before and after surgical correction of developmental dysplasia of the hip. Material and methods : We evaluated 78 children with developmental hip dysplasia treated at University Children’s Hospital in Belgrade during a 10-year period. Three age groups were analysed: the first group younger than 24 months of life, the second group between 25 and 48 months, and the third group older than 48 months of life. Three angles were evaluated separately before and after surgical correction: collodiaphyseal angle, Hilgenreiner angle and Wiberg’s centre-edge angle. Results : We found a highly statistically significant difference (p < 0.001) before and after the operation for collodiaphyseal and Hilgenreiner angle in the first and second age group, while there was a statistically significant difference (p < 0.05) in the third age group. Regarding Wiberg’s centre-edge angle, there was a highly statistically significant difference (p < 0.001) in all age groups. One way ANOVA revealed a highly statistically significant difference (p 0.05) between age groups of the participants. Conclusions : Our findings demonstrate that age of participants is in correlation with correction of values for collodiaphyseal angle, Hilgenreiner angle and Wiberg’s centre-edge angle in surgically treated children diagnosed with developmental dysplasia of the hip.